Commercial or Industrial Developments : Advice for Planning Officers and Applicants Seeking Planning Permission for Commercial or Industrial Developments Discharging to the Water Environment.: Advice for Planning Officers and Applicants Seeking Planning Permission for Commercial or Industrial Developments Discharging to the Water Environment. (2017) - Northern Ireland Environment Agency,
No abstract available